2009
DOI: 10.1007/s10897-009-9219-y
|View full text |Cite
|
Sign up to set email alerts
|

An Investigation of Relationships among Genetic Counselors’ Supervision Skills and Multicultural Counseling Competence

Abstract: As racial and ethnic diversity increase in the U.S., genetic counselor multicultural competence is growing in importance. In mental health counseling, supervisor multicultural competence has been shown to promote supervisees' multicultural competence. Moreover, developmentally-advanced supervisors tend to be more effective. This study was designed to investigate relationships among genetic counselor supervisors' perceived multicultural counseling competence and development as supervisors, and their ability to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 34 publications
0
11
1
Order By: Relevance
“…The plurality of papers in the GC supervision field are surrounding some of these difficulties. These six papers included the following: compassion fatigue/burnout from being a supervisor (Allsbrook et al, ), boundary issues (Gu, McCarthy Veach, Eubanks, LeRoy, & Callanan, ), multiculturalism/competence (Kyung Lee, McCarthy Veach, & LeRoy, ), anxiety (MacFarlane, McCarthy Veach, Grier, Meister, & LeRoy, ), games (McIntosh, Dircks, Fitzpatrick, & Shuman, ), and language issues (Vanneste et al, ). Each of these papers explored difficult aspects of the GC supervisor/student relationship, but all either suggest increasing the supervision working alliance or working with the GC program to identify ways to leverage existing resources to provide supervision training.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The plurality of papers in the GC supervision field are surrounding some of these difficulties. These six papers included the following: compassion fatigue/burnout from being a supervisor (Allsbrook et al, ), boundary issues (Gu, McCarthy Veach, Eubanks, LeRoy, & Callanan, ), multiculturalism/competence (Kyung Lee, McCarthy Veach, & LeRoy, ), anxiety (MacFarlane, McCarthy Veach, Grier, Meister, & LeRoy, ), games (McIntosh, Dircks, Fitzpatrick, & Shuman, ), and language issues (Vanneste et al, ). Each of these papers explored difficult aspects of the GC supervisor/student relationship, but all either suggest increasing the supervision working alliance or working with the GC program to identify ways to leverage existing resources to provide supervision training.…”
Section: Resultsmentioning
confidence: 99%
“…The main outcome measure that has been used in GC supervision literature is that of self‐efficacy, which is the perception of one's own ability. It has been used to measure: confidence in multiculturalism skills (Kyung Lee et al, ); confidence and competence as supervisors correlated to supervision experience and formal supervision training (Atzinger et al, , ; Finley et al, ); and student perceptions of their own training (Caldwell et al, ). A problem, though, is that self‐efficacy does not necessarily mean that someone is competent — it means they feel competent.…”
Section: Discussionmentioning
confidence: 99%
“…Of the 8 studies that reported information on degrees, 830 (64%) participants had doctorates. The participants varied in their professional backgrounds, and included supervisors who were psychologists (Vidlak, 2002;Watkins et al, 1995), supervisors from university counseling centers (Hillman et al, 1998), marriage and family therapists (Bencivenne, 1999), doctoral students (Baker, Exum, & Tyler, 2002), predoctoral interns (Lyon et al, 2008), counseling education supervisors (Barnes, 2002;Pelling, 2008), substance abuse counselor supervisors (Culbreth & Cooper, 2008), and genetic counselors (Lee, Veach, & LeRoy, 2009). Mean years of supervision experience was 10.2 across the 7 studies that reported this data.…”
Section: Overview Of Studiesmentioning
confidence: 99%
“…Of the 10 studies reviewed, 5 (50%) (Barnes, 2002;Lee et al, 2009;Lyon et al, 2008;Pelling, 2008;Watkins et al, 1995) studies reported internal consistency statistics (Cronbach's alpha) based on the study sample's scores. Of the five studies that did not report an alpha value (Baker et al, 2002;Bencivenne, 1999;Culbreth & Cooper, 2008;Hillman et al, 1998;Vidlak, 2002), each referenced the original PSDS alpha value and two of these studies also referenced other reliability statistics of an early follow-up study on the PSDS scale (Hillman et al, 1998).…”
Section: Reliability Generalizationmentioning
confidence: 99%
See 1 more Smart Citation